2006
DOI: 10.1039/b510101h
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of mesoporous materials with long alkyl chains as a strategy for controlling drug delivery pattern

Abstract: Mesoporous silica SBA-15 was prepared to evaluate its effectiveness as a matrix for the controlled delivery of macrolide-type antibiotics. Two types of material were used to evaluate the delivery: calcined samples and samples functionalized with octyltrimethoxysilane and octadecyltrimethoxysilane. The samples were charged with the macrolide antibiotic erythromycin and the release assays were carried out in vitro. It has been observed that the release rate decreases as the population of hydrophobic -CH 2 moieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
191
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(200 citation statements)
references
References 14 publications
(12 reference statements)
5
191
0
4
Order By: Relevance
“…Further, the formation of bonds could overcome the problems associated with the burst release of the incorporated drug molecule [3]. Doadrio et al have reported that erythromycin release from functionalized matrices was much slower compared to unmodified material [9]. Basaldella and Legnoverde have reported that the initial release of cephalexin was not influenced by functionalization of SBA-15 carrier but the second stage of the release was significantly influenced [10].…”
mentioning
confidence: 99%
“…Further, the formation of bonds could overcome the problems associated with the burst release of the incorporated drug molecule [3]. Doadrio et al have reported that erythromycin release from functionalized matrices was much slower compared to unmodified material [9]. Basaldella and Legnoverde have reported that the initial release of cephalexin was not influenced by functionalization of SBA-15 carrier but the second stage of the release was significantly influenced [10].…”
mentioning
confidence: 99%
“…By using this method, drug release from the matrix is increased because of inability of aqueous medium to penetrate into the pores but the drug-surface interactions remain same. Maria ValletRegi et al incorporate erythromycin in SBA-15 material containing hydrophobic species [15]. Treatment of the mesoporous silica material with trimethoxyoctylsilnane and trimethoxyoctadecylsilane resulted into functionalized surfaces of octyl and octadecyl moieties, respectively.…”
Section: Functionalization Of Mesoporous Silica Nanoparticlesmentioning
confidence: 99%
“…Diaz and Balkus [14] demonstrated that the large molecules like proteins can be immobilized in mesoporous material. Similarly, Vallet-Regi et al illustrates the loading and slow release of ibuprofen (IBU) from mesoporous silica material in solution [10,15]. The interior pores of MSNs facilitate loading of organic molecules such as MRI contrast agents and fluorescent as well for delivery of drug DNA and RNA.…”
Section: Introductionmentioning
confidence: 99%
“…The surface of these nanoparticles was modified to become compatible with the structure-directing agent (cetyltrimethylammonium). However, these approaches result in materials presenting two main limitations: (i) due to the use of ionic surfactants, they present typical wall thicknesses around 1 nm (Doadrio et al, 2006) and consequently, low stability; (ii) the functionalization of the mesoporous surface and nanoparticle surface leads to a decrease in the pore size and surface area (Alvaro et al, 2006), facts that could affect the applicability of such materials in adsorption systems, like drug delivery systems. In this context, we reported the synthesis of mesoporous SiO 2 -coated Fe 3 O 4 nanoparticles by using a neutral surfactant and without the application of any functionalization method (Souza et al, 2008).…”
Section: Advances In Diverse Industrial Applications Of Nanocompositementioning
confidence: 99%